Sosialisasi serta Edukasi Aplikasi Pengolahan Pangan Fungsional dalam Pencegahan Stunting Di Kecamatan Tanjung Morawa - Henni Cintya; Denny Satria; Mahatir Muhammad (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Stunting is the impaired growth and development that children experience from poor nutrition, repeated infection, and inadequate psychosocial stimulation. Stunting is an issue that has a big impact. Infants and toddlers may experience morbidity and death in the near term as a result. Low intellectual and cognitive capacities can be caused over the long term, as well as problems with degenerative diseases and the lowest quality adult human resources. The average prevalence of stunting toddler in Indonesia in 2015-2017 was 31.4%, far above the WHO limit of 20%. Based on this idea, this community service was carried out with the aim of educating mothers with the family walfare movement community (FWMC) about the importance of knowledge on how to process food from natural ingredients such as Moringa leaves and pumpkin into cookies as functional food for stunting prevention in childrens in Tanjung Morawa Regency. This activity received a very good response and high enthusiasm from FWMC and headmans. This activity was attended by 35 participants consisting of 25 mothers and 10 people as headman. Furthermore, an observation survey was conducted by providing questionnaires to measure the level of understanding of food processing from natural ingredients as functional foods for the prevention of stunting in children. Observations showed that arround 96% of mothers after participating in this activity knew what stunting was, the causes, prevention of stunting and how to process food as functional foods that could reduce the prevalence of stunting in Buntu Bedimbar Village, so that they could apply in their respective households for the health.